2012
DOI: 10.1186/1472-6785-12-19
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting habitat associations of imperilled endemic stream fishes from a global biodiversity hot spot

Abstract: BackgroundKnowledge of the factors that drive species distributions provides a fundamental baseline for several areas of research including biogeography, phylogeography and biodiversity conservation. Data from 148 minimally disturbed sites across a large drainage system in the Cape Floristic Region of South Africa were used to test the hypothesis that stream fishes have similar responses to environmental determinants of species distribution. Two complementary statistical approaches, boosted regression trees an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…‘Breede’. Chakona & Swartz [76] reported that Sandelia lineages in undisturbed tributaries of the Breede River system are restricted to river reaches below 425 m elevation, while Galaxias sp. ‘nebula’ and Pseudobarbus sp.…”
Section: Discussionmentioning
confidence: 99%
“…‘Breede’. Chakona & Swartz [76] reported that Sandelia lineages in undisturbed tributaries of the Breede River system are restricted to river reaches below 425 m elevation, while Galaxias sp. ‘nebula’ and Pseudobarbus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Fine‐scale geographic sampling approaches and recent phylogeographic studies have facilitated more accurate mapping of the distribution ranges of stream fishes in the CFE (Chakona and Swartz ; Chakona et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…Fine-scale geographic sampling approaches and recent phylogeographic studies have facilitated more accurate mapping of the distribution ranges of stream fishes in the CFE (Chakona and Swartz 2012;). This study focused on three co-occurring taxa in the Upper Riviersonderend River: the recently described P. skeltoni , the Breede lineage of P. burchelli (hereafter P. burchelli sp.…”
Section: Study Speciesmentioning
confidence: 99%
“…‘nebula’ to exploit dispersal corridors across drainage divides can be attributed to a number of factors. This lineage penetrates to higher elevations in mountain tributaries of the CFR than other native fishes (Chakona & Swartz, ). Opportunities for temporary inter‐basin connections are more likely at higher elevations than in lower parts of the basin.…”
Section: Discussionmentioning
confidence: 99%